Inter‐laboratory Characterisation of Apatite Reference Materials for Oxygen Isotope Analysis and Associated Methodological Considerations. Issue 2 (22nd March 2022) - Wudarska, Alicja; Wiedenbeck, Michael; Słaby, Ewa; Lempart‐Drozd, Małgorzata; Harris, Chris; Joachimski, Michael M.; Lécuyer, Christophe; MacLeod, Kenneth G.; Pack, Andreas; Vennemann, Torsten; Couffignal, Frédéric; Feng, Dingsu; et al.
Abstract : Here we report on the oxygen isotope compositions of four proposed apatite reference materials (chlorapatite MGMH#133648 and fluorapatite specimens MGMH#128441A, MZ‐TH and ES‐MM). The samples were initially screened for 18 O/ 16 O homogeneity using secondary ion mass spectrometry (SIMS) followed by δ 18 O determinations in six gas source isotope ratio mass spectrometry laboratories (GS‐IRMS) using a variety of analytical protocols for determining either phosphate‐bonded or "bulk" oxygen compositions. We also report preliminary δ 17 O and Δ ' 17 O data, major and trace element compositions collected using EPMA, as well as CO3 2− and OH − contents in the apatite structure assessed using thermogravimetric analysis and infrared spectroscopy. The repeatability of our SIMS measurements was better than ± 0.25 ‰ (1 s ) for all four materials that cover a wide range of 10 3 δ 18 O values between +5.8 and +21.7. The GS‐IRMS results show, however, a significant offset of 10 3 δ 18 O values between the "phosphate" and "bulk" analyses that could not be correlated with chemical characteristics of the studied samples. Therefore, we provide two sets of working values specific to these two classes of analytical methodologies as well as current working values for SIMS data calibration. Key Points: Four potential apatite reference materials have been characterised for oxygen isotopes by SIMS and six GS‐IRMS laboratories. Determined δ 18 O values are method‐specific and show a significant offset between the laboratories employing differing analytical protocols. Non‐systematic variations between the datasets do not correlate with chemical characteristics of the studied samples.